Pengembangan Modul Digital Interaktif Menggunakan Canva pada Materi Infak dan Sedekah sebagai Penguatan Literasi Digital Siswa - Maghfirah, Ulfa; Jasiah, Jasiah (Lembaga Yasin AlSys, 2025)
People are highly motivated to create new things, such as teaching materials, along with the rapid development of technology. One of the innovations in teaching materials is the switch from printed modules to electronic modules, known as E-Modules. The aim of this article is to develop an effective and practical Interactive Digital Module for classroom learning by utilizing Canva. The method used in this research is Research and Development (R&D) with a 4D model. This research was carried out at MTs Terpadu Berkah Palangkaraya. The Digital Module is adjusted by conducting validity and practicality tests. Validation is carried out by media experts and material experts. The results of the media validation of the interactive digital module at MTs Terpadu Berkah Palangkaraya show that this module is valid with a media expert validation percentage of 86% and material expert validation of 83.33%. Meanwhile, the results of practical tests carried out at the research school showed that 82.5% of students gave positive responses. Thus, the use of Canva-based interactive digital modules at MTs Terpadu Berkah Palangkaraya can be considered valid and practical to apply in learning.